Magnetosphere-Ionosphere Coupling: Implications of Non-Equilibrium Conditions - Lockwood, Mike; Cowley, Stan W. H. (Frontiers in Astronomy and Space Sciences, 2022)
The response times of the coupled magnetosphere-ionosphere-thermosphere system are, on average, greater than the autocorrelation timescales of solar wind forcing. This means that the system is rarely, if ever, in equilibrium. Departures from equilibrium are a key component of the Expanding-Contracting Polar Cap (ECPC) model of convection excitation in both the magnetosphere and ionosphere, driven by the Dungey reconnection cycle of opening and re-closing magnetospheric field lines. Averaging over sufficiently long timescales reduces data to the equivalent of steady-state conditions, which hides the physical mechanisms involved and allows us to map electric fields from interplanetary space to the ionosphere–but this is not valid, either physically or generally, because of magnetic induction effects. Only for transient phenomena on sufficiently short timescales do the mechanisms associated with non-equilibrium fully manifest themselves. Nevertheless, because of both ever-changing solar wind conditions and Earth’s dipole tilt, eccentricity and rotation, the magnetosphere is always tending towards a perpetually-evolving equilibrium configuration and there are important implications of transient events for understanding the general behavior of the coupled magnetosphere-ionosphere-thermosphere system and its response to solar wind forcing. We here discuss one example: as a consequence of the importance of departures from equilibrium inherent in the ECPC model, the solar wind dynamic pressure PSW influences the magnetosphere-ionosphere convection response to the generation of open field lines by reconnection in the dayside subsolar magnetopause. We here demonstrate this effect in a statistical survey of observations and show that it is as predicted by the ECPC model and that, through it, PSW has an influence on flux transport in the magnetosphere-ionosphere system.